2017
DOI: 10.1016/s2155-8256(17)30125-4
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Review: Identifying Evolving and Emergent Regulatory Trends

Abstract: A number of studies have sought to place regulatory trends within a general systems framework to describe new and emergent trends, and issues facing nursing regulation. The nursing profession is not alone in seeking to monitor changes and trends in the regulatory environment. Such disciplines as medicine, physiotherapy, law, and accounting have also been active in this area

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Veloso et al (2015), Adams (2016Adams ( , 2017, and Benton (2017) have shown the dimensions of professional regulation have evolved. While Benton (2017) identified 25 trends from global data obtained through a bibliometric analysis of indexed papers originating from the very inception of professional regulation, Adams (2016Adams ( , 2017 focused specifically on how the concept of the public interest evolved over 150 years in Canada.Veloso et al (2015), in their sociological analysis of regulation and public interest relative to Portuguese health professions, noted that changes in healthcare delivery, technology use, and globalization may impact our evolving understanding of acting in the public interest. Beyond nursing and the health professions, other disciplines such as the Institute of Chartered Accountants in England and Wales (ICAEW) (2012) conducted comprehensive research and contend that many of their findings may be applicable to other regulated professions.…”
Section: Trends In Acting In the Public Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…Veloso et al (2015), Adams (2016Adams ( , 2017, and Benton (2017) have shown the dimensions of professional regulation have evolved. While Benton (2017) identified 25 trends from global data obtained through a bibliometric analysis of indexed papers originating from the very inception of professional regulation, Adams (2016Adams ( , 2017 focused specifically on how the concept of the public interest evolved over 150 years in Canada.Veloso et al (2015), in their sociological analysis of regulation and public interest relative to Portuguese health professions, noted that changes in healthcare delivery, technology use, and globalization may impact our evolving understanding of acting in the public interest. Beyond nursing and the health professions, other disciplines such as the Institute of Chartered Accountants in England and Wales (ICAEW) (2012) conducted comprehensive research and contend that many of their findings may be applicable to other regulated professions.…”
Section: Trends In Acting In the Public Interestmentioning
confidence: 99%
“…From a general legal perspective, Mousmouti (2018) contended there is a need to focus on the content of primary legislation and how effective it is in delivering its primary intent. Table 1 (modified from the analysis presented by Benton and George [2018]) summarizes how the dominant concepts related to acting in the public interest evolved and provides a high-level summary of some of the changes identified by the work of ICAEW (2012), Veloso et al 2015, Adams (2016Adams ( , 2017, and Benton (2017). Professions cannot be trusted to act in the public interest and therefore need oversight.…”
Section: Trends In Acting In the Public Interestmentioning
confidence: 99%
See 1 more Smart Citation